A framework for assessing the performance of health systems. - Murray, C. J. (World Health Organization, 2000)
Health systems vary widely in performance, and countries with similar levels of income, education and health expenditure differ in their ability to attain key health goals. This paper proposes a framework to advance the understanding of health system performance. A first step is to define the boundaries of the health system, based on the concept of health action. Health action is defined as any set of activities whose primary intent is to improve or maintain health. Within these boundaries, the concept of performance is centred around three fundamental goals: improving health, enhancing responsiveness to the expectations of the population, and assuring fairness of financial contribution. Improving health means both increasing the average health status and reducing health inequalities. Responsiveness includes two major components: (a) respect for persons (including dignity, confidentiality and autonomy of individuals and families to decide about their own health); and (b) client orientation (including prompt attention, access to social support networks during care, quality of basic amenities and choice of provider). Fairness of financial contribution means that every household pays a fair share of the total health bill for a country (which may mean that very poor households pay nothing at all). This implies that everyone is protected from financial risks due to health care. The measurement of performance relates goal attainment to the resources available. Variation in performance is a function of the way in which the health system organizes four key functions: stewardship (a broader concept than regulation); financing (including revenue collection, fund pooling and purchasing); service provision (for personal and non-personal health services); and resource generation (including personnel, facilities and knowledge). By investigating these four functions and how they combine, it is possible not only to understand the proximate determinants of health system performance, but also to contemplate major policy challenges.